2021
DOI: 10.21037/tro-20-62
|View full text |Cite
|
Sign up to set email alerts
|

The volume of low-dose thoracic irradiation influences systemic inflammation-immunity status after chemoradiation in esophageal cancer

Abstract: Background: Definitive chemoradiation is an essential treatment for non-operative thoracic esophageal cancer. However, it may trigger radiation-induced lymphopenia, impacting survival outcomes. The neutrophil-lymphocyte ratio (NLR) is an indicator of inflammatory status and survival outcomes. Here, we determined the association of clinical and dosimetric parameters with changes in hematological variables. Methods: We recruited 93 thoracic esophageal squamous-cell cancer patients who have completed definitive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is difficult to explain the whole picture of the pro- or anti-tumorigenic host response to cancer therapies with a simple NLR-h level [ 45 ]; however, it may still reflect dynamic immune alterations during treatment and predict further prognosis. RT has been correlated with negative effects on immunity in non-small cell lung cancer [ 46 ], and we found that the volume of low-dose thoracic irradiation affects systemic inflammation-immunity status, as the absolute lymphocyte count is the most correlated with decreasing blood cell count [ 47 ]. It has been proposed that radiation-induced lymphopenia impacts complete pathological response rates, and that the cardiac dose is a leading dosimetric factor associated with severe lymphopenia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain the whole picture of the pro- or anti-tumorigenic host response to cancer therapies with a simple NLR-h level [ 45 ]; however, it may still reflect dynamic immune alterations during treatment and predict further prognosis. RT has been correlated with negative effects on immunity in non-small cell lung cancer [ 46 ], and we found that the volume of low-dose thoracic irradiation affects systemic inflammation-immunity status, as the absolute lymphocyte count is the most correlated with decreasing blood cell count [ 47 ]. It has been proposed that radiation-induced lymphopenia impacts complete pathological response rates, and that the cardiac dose is a leading dosimetric factor associated with severe lymphopenia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%